A photoluminescent indium–organic framework with discrete cages and one-dimensional channels for gas adsorption. Issue 58 (19th January 2016) - Qian, Jinjie; Li, Qipeng; Liang, Linfeng; Yang, Yan; Cao, Zhen; Yu, Panpan; Huang, Shaoming; Hong, Maochun
Abstract : This microporous structure is a novel 3, 4, 4-connected structure simultaneously built from the mutually competitive [In(CO2 )4 ] and [Eu2 (CO2 )4 (H2 O)4 ] secondary building units together with the tricarboxylate ligand. Abstract : We have successfully obtained, for the first time, a new heterometallic indium–organic framework (InOF-14 ) with a functional and luminescent Eu(iii ) component. Based on the mutually competitive [In(CO2 )4 ] and [Eu2 (CO2 )4 (H2 O)4 ] units, this microporous structure possesses discrete nano-cages and one-dimensional channels for gas adsorption, and simultaneously exhibits excellent luminescence properties.